Return on Asset pada Perusahaan Sub Sektor Farmasi: Studi Pengaruh Sales Growth, Current Ratio dan Net Profit Margin - Nurfitria Nurfitria; Rosma Pakpahan; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to explain the effect of Sales Growh, Current Ratio, and Net Profit Margin on Return On Asset in pharmaceutical sub-sector companies listed on BEI in 2015-2020. The research method used is associative method with a quantitative approach. The source of data used is secondary data in the form of annual reports of pharmaceutical companies. Sampling technique is using porposive sampling technique and obtained a total sample of 6 pharmaceutical companies from 11 pharmaceutical companies listed on BEI in 2015-2020. The type of data used is panel dataa. Data analysis in this research is multiple linear regression using IBM SPSS Statisticss25 Software. The result showed that Sales Growth, Current Ratio (CR) and Net Profit Margin (NPM) Simultaneously have a significant effect on ROA. Partially, Sales Growth has a negative and insinigficant effect on ROA. While the Current Ratio(CR) and Net Profit Margin (NPM) have a positive and significant effect on ROA.